Annual report 2016: CGIAR Research Program on Agriculture for Nutrition and Health - CGIAR Research Program on Agriculture for Nutrition and Health (CGIAR Research Program on Agriculture for Nutrition and Health, 2017)
In its fifth and final year of Phase I, the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) has validated its core areas of research, taking many to scale while also broadening its Phase II portfolio. • By the end of 2016, more than 130 biofortified varieties of 10 crops were released in over 30 countries, all positive steps toward HarvestPlus’s goal of reaching 20 million farm households with biofortified crops by 2020 and 1 billion people consuming biofortified foods by 2030. High quality evidence—on topics such as emerging zoonoses, Rift Valley fever, aflatoxin control, and food safety in informal markets—helped inform policy and decision making to prevent and control agriculture-associated diseases in high-risk areas. Following a successful Nigeria pilot stage, the aflasafe™ approach for managing aflatoxins consistently reduced groundnut and maize aflatoxin contamination by at least 80 percent, with plans and investments to expand the approach to 11 other African countries. Rigorous evaluations of integrated agriculture-nutrition interventions demonstrated, for the first time, that well-designed programs can have measurable impacts on child and maternal nutrition, as well as on women’s empowerment. • A4NH’s work to raise the profile of nutrition globally includes highly cited outputs such as the annual Global Nutrition Reports, started in 2014 with input from A4NH researchers, which offer a global roadmap for accountability and action to address undernutrition. The innovative Stories of Change in Nutrition initiative raised the profile of the dynamics of nutrition change processes, and its associated set of resources, produced in 2016, were widely disseminated and applied. Lastly, A4NH researchers contributed significantly to the African Union’s Annual Trends and Outlook Report that focused, for the first time, on agriculture-nutrition linkages. • For Phase II, A4NH is eager to build upon success from Phase I while reframing its approach toward food safety, diet quality, and public health research with an expanded portfolio and exciting new partnerships.